Role of Small Pd Ensembles in Boosting CO Oxidation in AuPd Alloys - Ham, Hyung Chul; Stephens, J. Adam; Hwang, Gyeong S.; Han, Jonghee; Nam, Suk Woo; Lim, Tae Hoon (American Chemical Society, 2012)
We present a theoretical explanation on how PdAu alloy catalysts can enhance the oxidation of CO molecules based on density functional theory calculations of CO adsorption and oxidation on AuPd/Pd(111) surfaces. Our study suggests that the enhanced activity is largely attributed to the possible existence of "partially-poisoned" Pd ensembles that accommodate fewer CO molecules than Pd atoms. Whereas the oxidation of preadsorbed CO is likely governed by O-2 trapping, our study shows that small Pd ensembles such as dimers and compact trimers tend to provide more active sites than larger ensembles; CO adsorbed on a Pd monomer is found to react hardly with O-2 to form CO2. In addition, we find the tendency of CO-induced Pd agglomeration, which may in turn facilitate CO oxidation by creating more dimers and compact trimers as compared with the adsorbate-free surface where monomers are likely prevailing.